Proposing a model for assessing green hotels based on ecological indicators. (October 2020) - Bagheri, Moslem; Shojaei, Payam; Jahromi, Samaneh Asghari; Kiani, Mehrdad
The hospitality industry has undergone significant developments as new modes of environment-friendly tourism and hotels have emerged (including ecotourism, eco-hotels, ecolodges, and green hotels). These new features, however, have not been specifically investigated, especially in a considerably potential tourist destination like Iran. This study sought to develop a model for identifying and prioritizing the indicators that could determine the ecological features of hotels. Following a systematic review, exploratory factor analysis and analytic network process were used to construct a hybrid model and its elements were then prioritized in five-star hotels in the Fars province, Iran. The model consisted of five dimensions (totally including 19 indicators), namely "energy, " "ecological adaptation, " "materials and equipment, " "foods and drinks, " and "cultural-economic activities." The findings revealed that the "energy" dimension was significantly important, while indicators such as "effective use of water, " "supply and efficient use of energy, " and "use of renewable energies" were the most important indicators, respectively. The results of this study can encourage managers/practitioners in hotel accommodation to concentrate on the indicators that could promote the ecological level of hotels. In doing so, they can consider energy, foods, and beverage indicators in developing green hotels and implement appropriate accommodation with ecotourism standards to attract (inter)national tourists.